(untitled) (Journal of NAST College, 2025)
Seismic vulnerability assessment of non-engineered reinforced concrete (RC) buildings in Far Western Nepal, including Darchula, is crucial due to their inadequate structural performance under earthquake loading. These buildings, typically designed for gravity loads, often feature soft-story mechanisms caused by weak ground stories, making them highly susceptible to seismic failure. This study evaluates the seismic performance of three low-rise (5-story) RC structures using capacity curves, fragility curves, and failure mapping techniques. The capacity curve analysis reveals that NERcA exhibits the weakest base shear capacity, while NERcC shows the highest strength, indicating variations in construction quality and reinforcement detailing. Failure mapping demonstrates that plastic hinges form primarily in columns rather than beams, contradicting the column-weak-beam design philosophy, and soft-story failure is evident due to irregular stiffness distribution. Fragility analysis further highlights the high probability of failure at lower spectral displacements, with steep fragility curves indicating significant vulnerability, even under moderate seismic loads. The results underscore the need for seismic retrofitting, improved construction practices, and adherence to modern seismic codes to enhance structural resilience. Implementing these measures is critical to reducing seismic risks and preventing catastrophic failures in earthquake-prone regions.